Media Pembelajaran Tingkat Madrasah Ibtidaiyah Dalam Perspektif Psikologi Pendidikan - Setiyawan, Dimas; Ayu, Abidah (Prodi PGMI STIT Al-Ittihadiyah Labuhanbatu Utara, 2025)
The use of learning media at the elementary madrasah level has an important role in supporting the effectiveness of the teaching and learning process. However, in practice, the use of learning media is often not adjusted to the psychological development stage of students, who are still in the concrete operational phase. This mismatch can have an impact on low absorption of material, lack of learning motivation, and limited active involvement of students in learning. This study aims to examine learning media in elementary madrasahs from the perspective of educational psychology, with a focus on the suitability between the type of media used and the stage of student development. This study uses a qualitative approach with a type of library research. Data were collected through a review of various literature sources such as books, scientific journals, articles, and relevant official documents. Data analysis was conducted using content analysis method and source triangulation technique was used to ensure the validity of the data. The results of the study showed that the majority of teachers in elementary madrasahs still use conventional media and have not considered the psychological aspects of students in their selection. In addition, teachers' understanding of educational psychology is still limited, so that the media used is less than optimal in increasing the effectiveness of learning. This study suggests the need for the development of learning media based on educational psychology and teacher training to be able to design media that is in accordance with the developmental needs of students. The implications of this study can strengthen the direction of educational policies that are more oriented towards the psychological needs of children at the elementary level.